The Phoenix stellar stream rose from the ashes of an ancient star cluster - Kruijssen, Diederik (Nature, 2020)
Observations of a star system called the Phoenix stellar stream offer the first evidence of vanished star clusters that had extremely low levels of heavy elements. Their remnants might cast light on the early assembly of the Milky Way.
Gesehen am 28.09.2020